The Impact of High Foreign Flight Slot Time Requests on National Flights - Setiawan, Ariyono; Tri Prasetyo , Kukuh; Ardian, Dede; Manaricha, Anti; Larasati, Khoirunnisa (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Flights are one of the most effective and efficient modes of transportation to reach distant travel destinations. Slot time is the time specified for a flight to land or take off from an airport. The purpose of this study is to find out how changes in the number of foreign flight slots available in a country can affect the national aviation industry. This research was conducted by the method of literature study or literature review. The results suggest that an increase in foreign flight time slots will probably have a negative impact on national flights at the same airport, especially if there is not enough planning to manage congestion at those airports. If the time slot of foreign flights increases, then there may be more foreign flights that will land or take off from that airport, which can cause overcrowding at the airport and reduce the time slot available for national flights.